AVALIAÇÃO DE ESPÉCIES FLORESTAIS COM VISTAS A RECUPERAÇÃO DE UMA ÁREA DEGRADADA NA UEMS-AQUIDAUNA. - POLINI, Paula de Sousa; PINHEIRO, Marina Ferreira Soares; CAPPI, N.; ABRANTES, Karen Keli Barbosa; AVALO, Kenedy Pereira (ANAIS DO ENIC, 2017)
-